Avaliação dos valores lean management e sua influência em práticas sustentáveis em instituições de ensino superior – IES - Feltrin, Thiago Schirmer (2021)
The Lean philosophy and sustainability have been discuted recently in studies and research in Higher Education Institutions - HEIs. The Lean philosophy aims to eliminate waste and generate value for the target audience and also a management philosophy that involves the use of various tools and techniques for efficiency of internal and external processes. Sustainability concerns the impact of human beings on the planet and indicates how human beings should act responsibly with each other, with future generations and with nature. Thus, these two thematic axes aim at improving existing processes in Higher Education Institutions – HEIs to improve the efficiency of sustainability. In this sense, this research aims to evaluate the practices and values of Lean management in HEIs and its influence on sustainability practices. The theoretical basis of the work is supported by the definition of Lean and sustainable practices, which are used to outline the research model. The work method consists of a quantitative research characterized as a survey, whose data collection was carried out through a questionnaire. The study population are servers and employees of Higher Education Institutions - HEIs in Brazil. A final valid sample of 868 responses was obtained. Data analysis was performed using descriptive statistics, exploratory factor analysis, confirmatory factor analysis and structural equation modeling. The results allow us to assess a significant and positive relationship between the second-order construct called Lean Practices in Higher Education Institutions - HEIs and environmental, economic and social sustainability practices. These findings demonstrate the relevance of aspects such as leadership and systemic vision as support to workers, continuous improvement and the elimination of waste as a daily practice, and long-term thinking and the focus on the student as basic elements of the success of Higher Education Institutions – HEIs for the promotion of sustainability practices.